Strategi Pengembangan Kurikulum dalam Meningkatkan Mutu Membaca Kitab Kuning di Madrasah Tsanawiyah Fattah Hasyim Bahrul ‘Ulum Tambakberas Jombang - Muhammad Rizki; Abdullah Asyiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to identify and analyze curriculum development strategies that can effectively improve the quality of yellow book reading in the Madrasah Tsanawiyah Fattah Hasyim Tambakberas Jombang. The yellow book has an important role in Islamic education, and the success of its learning can reflect the quality of education at the institution. The research method used is qualitative research with a case study approach. Data was obtained through observation, interviews and analysis of documents related to the existing curriculum. Respondents involved teachers who taught the yellow book and students from Madrasah Tsanawiyah Fattah Hasyim. The research results show that there are challenges in learning the yellow book, such as the lack of student interest and the lack of variety in learning methods. Therefore, curriculum development strategies need to be formulated and implemented to improve the quality of reading the yellow book. Some of the recommended strategies involve increasing interactive learning methods, using technology to support learning, and involving students in curriculum development. Apart from that, an emphasis on increasing yellow book literacy through extracurricular activities and building teacher competency is also an integral part of the curriculum development strategy. It is hoped that the results of this research can make a positive contribution to the development of Islamic education at Madrasah Tsanawiyah Fattah Hasyim Tambakberas Jombang and provide inspiration for similar educational institutions to improve the quality of yellow book learning.